2017
DOI: 10.1186/s13104-017-3090-y
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-associated microRNA changes in circulating exosomes of heart failure patients

Abstract: ObjectiveMiR-486 and miR-146a are cardiomyocyte-enriched microRNAs that control cell survival and self-regulation of inflammation. These microRNAs are released into circulation and are detected in plasma or in circulating exosomes. Little is known whether heart failure affects their release into circulation, which this study investigated.ResultsTotal and exosome-specific microRNAs in plasma of 40 heart failure patients and 20 controls were prepared using the miRVana Kit. We measured exosomal and total plasma m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 43 publications
0
43
1
1
Order By: Relevance
“…Circulating miRNAs are unusually stable due to (1) their packaging in vesicles, such as in exosomes (Chugh et al, 2013) or apoptotic bodies, (2) their RNA folding and size, and/or (3) their presence in Ago-containing ribonucleic acid: protein (RNP) complexes (Chugh et al, 2013), with nucleophosmin (Kubiczkova et al, 2014), or with high-density lipoproteins (HDL) (Köberle et al, 2013;Fornari et al, 2015). The stability of miRNAs results from their resistance toward the action of ribonucleases (Jansen et al, 2014;Dinh et al, 2016;Beg et al, 2017;Liu et al, 2017a;Yokoi et al, 2017;de Candia et al, 2013;Li et al, 2012). This stability means that they are long-lived in biological fluids (Ragusa et al, 2015;Emanueli et al, 2016) and are therefore proposed as attractive diagnostic (Pirola et al, 2015) and prognostic biomarkers (Fornari et al, 2015).…”
Section: Factors Contributing To the Stability Of Circulating Mirnas mentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating miRNAs are unusually stable due to (1) their packaging in vesicles, such as in exosomes (Chugh et al, 2013) or apoptotic bodies, (2) their RNA folding and size, and/or (3) their presence in Ago-containing ribonucleic acid: protein (RNP) complexes (Chugh et al, 2013), with nucleophosmin (Kubiczkova et al, 2014), or with high-density lipoproteins (HDL) (Köberle et al, 2013;Fornari et al, 2015). The stability of miRNAs results from their resistance toward the action of ribonucleases (Jansen et al, 2014;Dinh et al, 2016;Beg et al, 2017;Liu et al, 2017a;Yokoi et al, 2017;de Candia et al, 2013;Li et al, 2012). This stability means that they are long-lived in biological fluids (Ragusa et al, 2015;Emanueli et al, 2016) and are therefore proposed as attractive diagnostic (Pirola et al, 2015) and prognostic biomarkers (Fornari et al, 2015).…”
Section: Factors Contributing To the Stability Of Circulating Mirnas mentioning
confidence: 99%
“…The source of miRNAs being the cause of variation in results can be seen in a study reported by Huang et al (2017; tissues versus circulating miRNAs) and a study by Reithmair et al (2017; cellular versus vesicle or cell-free miRNAs). The second limitation is lacking a large sample size and validation of results in different independent cohorts (Gallo et al, 2012;Momen−Heravi et al, 2015;Dinh et al, 2016;Jansen et al, 2016;Beg et al, 2017;Huang et al, 2017;Khare et al, 2017;Liu et al, 2017a;Rabinowits et al, 2017;Yokoi et al, 2017). The sample size in biomarker studies is usually only suitable for a pilot study.…”
Section: Limitations In Mirna Biomarker Studiesmentioning
confidence: 99%
“…NF-kappaB increases the expression of miR-146a, which inhibits the action of the IL-1 and TNF-alpha receptors, thereby decreasing inflammation. For this reason, the cardioprotective effect of miR-146a has been highlighted recently [90]. Lately, a trend towards elevated plasma concentration of miR-146a and miR-486 has been demonstrated in a group of patients with HF when compared with a control group [90].…”
Section: The Participation Of Micro-rna In Inflammation In Hfmentioning
confidence: 99%
“…For this reason, the cardioprotective effect of miR-146a has been highlighted recently [90]. Lately, a trend towards elevated plasma concentration of miR-146a and miR-486 has been demonstrated in a group of patients with HF when compared with a control group [90]. In addition, NF-kappaB reduces the level of muscle-specific transcription factor (MyoD).…”
Section: The Participation Of Micro-rna In Inflammation In Hfmentioning
confidence: 99%
See 1 more Smart Citation